MYOFASCIAL PAIN SYNDROME: UPDATED INSIGHTS ON CLINICAL FEATURES, CAUSES, DIAGNOSIS, AND EVIDENCE-BASED TREATMENT APPROACHES - MADHAVI SELUKAR; SUREKHA GODBOLE; SHARAYU NIMONKAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Myofascial pain syndrome (MPS) is a widespread musculoskeletal disorder characterized by localized pain, tenderness, and dysfunction arising from myofascial trigger points (MTrPs). This examines offers a modified synopsis of clinical views within MPS, stresses their epidemiology, pathogenesis, diagnostic standards, and evidence-based management methods. Epidemiological statistics reveal a variety of prevalence in general societies and higher rates in chronic pain clinics, oncology patients, and patients with comorbid conditions such as fibromyalgia. Hazard variables: Duration material, systemic, psychological, and lifestyle. Etiopathogenesis involves an intertwined mechanism involving MTrP formation arranged for peripheral nociception, fundamental sensitization magnifying pain and neurogenic inflammation, preserving muscle hyperirritability. In clinical practice, MPS can be described as localized pain caused by contact with the body, restriction of movement, and partner sleep disturbance. Trust in standardized standards, clinical palpation of MTrPs, and rejection of mimics. Pharmacological therapy, such as non-steroidal anti-inflammatory drugs, antidepressants, and muscle relaxants, has modest efficacy, while non-pharmacological interventions, such as dry needling, manual therapy, and neuromuscular techniques, have more evidence of lowering pain and improving function. However, growth therapy appreciates shockwave therapy and neuromodulation, which still require validation. A multimodal, patient-centered strategy integrating pharmacological and non-pharmacological modes of action according to the profile of the patient and the comorbidities should be highlighted. Although progress has been made, differences remain in the understanding of long-term effects, optimal treatment planning, and biomarker designation. Future research should prioritize large-scale randomized trials, biomarker discovery, and personalized medicine frameworks to enhance clinical decision-making and patient outcomes. This review underscores the need for a holistic, evidence-driven strategy to address the complex interplay of biopsychosocial factors in MPS.